Analisis Pengaruh Asuransi Ekspor LPEI terhadap Kinerja Ekspor Indonesia - Sharon, Otniel (PT Literasi Nusantara Publisher, 2024)
Exporting carries risks such as geopolitical and commercial risks. Data from LPEI (Indonesian Export Credit Agency) indicates that the Covid-19 pandemic has led to a two to threefold increase in default cases by foreign buyers (Arfiana, 2023). One way to mitigate export risks is by using export insurance. LPEI has been tasked by the government to promote exports through its products, one of which is export insurance based on Law No. 2 of 2009. This research is conducted with the aim of assessing whether export insurance products have successfully increased Indonesia's exports to its top 10 destination countries: China, the United States, Japan, South Korea, Thailand, Singapore, Malaysia, the Philippines, Taiwan, and India. The research methodology employs a gravity model. The dependent variables used are Indonesia's export value to these five countries. The independent variables include LPEI export insurance exposure, economic distance, GDP per capita of Indonesia and the destination countries, nominal exchange, and import tariffs of the destination countries. The research findings indicate that export insurance, GDP per capita, exchange rates and economic distance have a significant positive impact on export value, while and import tariffs have a significant negative impact on export value.